2020
DOI: 10.1021/acsomega.0c05172
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Combustion Characteristics of Wetting Coal under Different Prepyrolysis Temperatures

Abstract: The influence of prepyrolysis temperatures on the spontaneous combustion of wetting coal remains unclear from a macroscopic perspective. To this end, a low-ash and high-volatile wetting coal sample from Western China was pretreated by a programmed heating experimental system at isothermal pyrolysis temperatures of 50, 80, 110, 140, and 170 °C under nitrogen atmosphere and then cooled to room temperature; after that, the oxidation heating experiment was carried out within the range of 30–170 °C. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The period of steady growth (2009-2019) was an important phase in the global MFPC research journey, which lasted for a decade, and the annual publication volume in the field showed a continuous and steady increase, with an average of about 25 academic articles published each year [51][52][53][54][55]. During the explosive growth period (2020 to 2023), the average number of papers published in the direction of MFPC in this stage is 107 per year, and the number of papers has surged [56][57][58][59][60][61][62][63]. The main reason is that the research in MFPC field continues to deepen, resulting in an increasing number of fruitful results accumulated by researchers, which not only build a solid foundation for subsequent research but also indicate the direction of research.…”
Section: Year-to-year Trends In the Number Of Articles Issuedmentioning
confidence: 99%
“…The period of steady growth (2009-2019) was an important phase in the global MFPC research journey, which lasted for a decade, and the annual publication volume in the field showed a continuous and steady increase, with an average of about 25 academic articles published each year [51][52][53][54][55]. During the explosive growth period (2020 to 2023), the average number of papers published in the direction of MFPC in this stage is 107 per year, and the number of papers has surged [56][57][58][59][60][61][62][63]. The main reason is that the research in MFPC field continues to deepen, resulting in an increasing number of fruitful results accumulated by researchers, which not only build a solid foundation for subsequent research but also indicate the direction of research.…”
Section: Year-to-year Trends In the Number Of Articles Issuedmentioning
confidence: 99%
“…Pis et al investigated the effect of preoxidation on the early autothermal behavior of coal using differential thermal analysis. Wang et al concluded that the characteristic parameters, such as exotherm, gas products, and the apparent activation energy of coal, more significantly changed after preoxidation. Tang et al studied the mass and heat changes after preoxidation and concluded that preoxidation increases the risk of spontaneous combustion of lignite, but excessive preoxidation temperatures have the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 16 adopted TG/DSC-FTIR to analyze the macroscopic characteristics of functional groups in the process of coal spontaneous combustion, which indicates that −OH is the most active group in coal spontaneous combustion. Wang et al 17 investigated the influence of pre-pyrolysis temperatures on the spontaneous combustion characteristics of wetting coal. Xu et al 18 studied the combustion (secondary oxidation) characteristics of jet coal after oxidation and water immersion, and the results showed that water immersion had both inhibition and promotion effects on spontaneous combustion.…”
Section: Introductionmentioning
confidence: 99%